Supporting Finite Element Analysis with a Relational Database Backend; Part III: OpenDX "” Where the Numbers Come Alive - Heber, Gerd; Pelkie, Chris; Dolgert, Andrew; Gray, Jim; Thompson, David (2005)
In this report, we show a unified visualization and data analysis approach to Finite Element Analysis. The example application is visualization of 3D models of (metallic) polycrystals. Our solution combines a mature, general purpose, rapid-prototyping visualization tool, OpenDX (formerly known as IBM Visualization Data Explorer) [1,2], with an enterprise-class relational database management system, Microsoft SQL Server [3]. Substantial progress can be made with established off-the-shelf technologies. This approach certainly has its limits and we point out some of the shortcomings which require more innovative products for visualization, data-, and knowledge management. But, overall, the approach is a substantial improvement in the FEA lifecycle, and probably will work for other data-intensive sciences wanting to visualize and analyze massive simulation or measurement datasets.